GIS and Security System: A Case Study of Bank Robbery - and Zubairul Islam, R. P. Singh, (Recent Research in Science and Technology, 2010)
Security has been major concern of mankind for decades. Various techniques have introduced to provide possible solutions and this list is growing everyday. Most of these techniques are preventive and are mainly used to raise alarms. With growing knowledge and advancement in GIS and GPS technologies there is a possibility of new set of techniques that along with preventive services can provide tracking and control services.